1998
DOI: 10.1042/bst026s142
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of docosahexaenoic acid in red blood cell membranes of depressive patients

Abstract: It has beem hypothesised that a depletion Of omega-3 PUFAs, particularly DHA, may be of aetiologic importance in depression This hypothesis is supported by epidemiological observationsand limited clinical data. We have fiuther investigated the hypothesis [2].PUFA composition of phospholipids in RBC membranes fiom 10 depressed cases and 14 matched controls were measured. Current dietary intake of PUFAs was also measured using the 7day weighed intake method.It was found that total omega3 PUFAs, EPA and DHA level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 2 publications
1
30
0
Order By: Relevance
“…One study again found negative associations between n-3PUFA intake and depression (64) , although no association between n-3PUFA intake and a number of depressive illnesses and behaviours has also been reported (61,78,79) . These studies, however, are typically small, often fail to account adequately for confounding factors as above, and due to the difficulty of accurately measuring usual diet, are far from conclusive.…”
Section: Self-report Depressed Mood (Hads-d Cut-off 4/5)mentioning
confidence: 99%
See 1 more Smart Citation
“…One study again found negative associations between n-3PUFA intake and depression (64) , although no association between n-3PUFA intake and a number of depressive illnesses and behaviours has also been reported (61,78,79) . These studies, however, are typically small, often fail to account adequately for confounding factors as above, and due to the difficulty of accurately measuring usual diet, are far from conclusive.…”
Section: Self-report Depressed Mood (Hads-d Cut-off 4/5)mentioning
confidence: 99%
“…(1998) (63) C major depression (64) C major depression (65) C major depression (66) C and SC major depression (67) C major depression in ACS patients (68) C major depression in ACS patients (69) C depression in MI patients (70) C postpartum (71) C major depression (72) C major depression (74) NC adolescent depression (75) NC depression in lung cancer patients…”
Section: Trial Evidencementioning
confidence: 99%
“…Studies of plasma and red blood cell membrane phospholipid content of fatty acids in depressed subjects have shown reduced content of EPA and DHA [Adams et al, 1996;Edwards et al, 1998;Peet et al, 1998;Maes et al, 1999]. In some settings, this reduced membrane content of EPA and DHA in depression may be a state phenomenon related to low dietary availability [Tanskanen et al, 2001] or the increased requirement during pregnancy, particularly of DHA, for fetal neural development [Hibbeln, 2002].…”
Section: Introductionmentioning
confidence: 97%
“…However, only a few studies have focused on dietary factors, a fact which shows their underestimated recognition in research on depression. Lower concentrations of 3 have been reported in the plasma/red blood cell membranes of persons with major depressive disorder diagnosis compared with matched non-depressed control subjects [41][42][43]. Tiemeier et al [44] found in a group of 567 participants statistically significant lower 3 PUFAs levels, and higher 6/ 3 ratios in blood serum in individuals with depressive disorder than in the non-depressed control group.…”
Section: Nutrients and Affective Functionmentioning
confidence: 98%